2011
DOI: 10.1038/jhh.2011.3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of elevated blood pressure and consumption of dairy foods

Abstract: Hypertension is a public health priority in developed countries and worldwide, and is strongly associated with increased risk and progression of cardiovascular and renal diseases. A systematic review and metaanalysis were conducted to examine the association between dairy food intake during adulthood and the development of elevated blood pressure (EBP), specifically comparing the association of EBP with consumption of low-fat dairy foods versus high-fat dairy foods, as well as cheese versus fluid dairy foods (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
140
1
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(164 citation statements)
references
References 37 publications
(80 reference statements)
12
140
1
10
Order By: Relevance
“…Our results concurred with a metaanalysis of 5 prospective cohort studies conducted among populations in the United States and Europe, which found a significant 13% reduction in hypertension risk comparing the highest with the lowest category of total dairy intake (14). However, the dosage substantially varied in different studies: Heart Study in the United States indicated a significant 8% risk reduction in hypertension with each 1-serving/wk increase in total dairy product intake, but the corresponding association for each 1-serving/wk increase in fluid milk was null (10).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results concurred with a metaanalysis of 5 prospective cohort studies conducted among populations in the United States and Europe, which found a significant 13% reduction in hypertension risk comparing the highest with the lowest category of total dairy intake (14). However, the dosage substantially varied in different studies: Heart Study in the United States indicated a significant 8% risk reduction in hypertension with each 1-serving/wk increase in total dairy product intake, but the corresponding association for each 1-serving/wk increase in fluid milk was null (10).…”
Section: Discussionsupporting
confidence: 91%
“…This makes an opportunity to investigate the potential association with the risk of hypertension at a lower range of dairy intake. Some dietary guidelines (14,24) recommend consumption of 2-3 cups of dairy/d. Our study suggests that 1 cup milk/d may also be protective against hypertension in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of total dairy intake may not reveal the underlying relationships between milk and cardiometabolic risk in adolescents. Furthermore, the lack of association observed between CMRS and cheese may be, in part, explained by the higher fat, sodium, and lower potassium held by cheese compared with milk and other fluid dairy food [38]. On the other hand, the preponderance of evidence, mostly in adults, indicates that milk intake is more likely to be associated with beneficial cardiometabolic outcomes [13], [39], [40] and [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential health impacts of animal-derived foods, and more specifically Proceedings of the Nutrition Society milk and dairy consumption, have been questioned owing to their high saturated fat content (for review, see (3) ). However, emerging epidemiological evidence supports the beneficial effects of milk and dairy consumption on health, particularly cardiometabolic health (4)(5)(6) .…”
Section: Dairy Protein: Metabolic Health: Blood Pressure: Vascular Fumentioning
confidence: 99%